Indigenous Communities and Settler Colonialism Land Holding, Loss and Survival in an Interconnected World - Laidlaw, Zoë.; Lester, Alan.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
The new world created through Anglophone emigration in the 19th century has been much studied. But there have been few accounts of what this meant for the Indigenous populations. This book shows that Indigenous communities tenaciously held land in the midst of dispossession, whilst becoming interconnected through their struggles to do so.
Keywords: Civilization-History.; Imperialism; Social history; History, Modern; World history; Cultural History; Imperialism and Colonialism; Social History; Modern History; Theories of Law, Philosophy of Law, Legal History; World History, Global and Transnational History